Information System Strategic Planning at PT EP-TEC Solutions Indonesia - Andry Adrian Tirana (The Winners, 2019)
This research aimed to analyze the internal and external environment of business and information system /information technology (IS/IT), to identify current and future application portfolios, and to develop an Information System Strategic Planning to achieve the vision, mission, and objectives of PT EP-TEC Solutions Indonesia. The data were obtained from the results of interviews, observations, literature study, questionnaires, and analysis of the company’s internal documents. Data were taken from interviewing and questionnaires that were ten managerial levels of 50 employees at PT EP-TEC Solutions Indonesia. The weight on the SWOT IFAS and EFAS matrix used a pairwise comparison method. The method applied descriptive method by using the Information System Strategic Planning framework from Ward and Peppard. The analytical tools used Porter’s Five Forces, PEST, SWOT, Value Chain, IT Balance Scorecard, and McFarlan Strategic Grid. The results of this research indicate that future application portfolio recommendation that supports SI business strategies, IS/IT management strategies, and IT strategies that can help PT EP-TEC Solutions Indonesia in achieving strategic goals. From these results, it can be concluded that there are several proposals for applications, security tools, profiles of knowledge and skills, and recommendations for IS/IT infrastructure that can be applied in the company.